1993
DOI: 10.1080/01635589309514295
|View full text |Cite
|
Sign up to set email alerts
|

Antigenotoxic properties of lactic acid bacteriain vivoin the gastrointestinal tract of rats

Abstract: In view of the high incidence of dietary-related tumors, one important research goal is to identify the participating genotoxic carcinogens and the nutritional factors that may counteract their activities. We therefore have further developed a method to assess DNA damage in tumor target tissues of the gastrointestinal tract. Subsequently the prevention of this inducible DNA damage by lactic acid bacteria and by milk products fermented with probiotics was studied as well. The microgel electrophoresis technique … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
29
0

Year Published

1997
1997
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(34 citation statements)
references
References 17 publications
5
29
0
Order By: Relevance
“…Lactic acid bacteria (LAB) and their fermented products are thought to confer a variety of important nutritional and therapeutic benefits (e.g., relief of lactose maldigestion, antidiarrhoeal capabilities) [Tuohy et al, 2003]. Moreover, some fermented dairy products and/or LAB have demonstrated antimutagenic/antigenotoxic acti-vities both in vitro and in vivo [Bodana and Rao, 1990;Renner and Munzner, 1991;Hayatsu and Hayatsu, 1993;Pool-Zobel et al, 1993a,b, 1996Villarini et al, 1997;Villarini and Pasquini, 1999] as well as antitumor properties [Hirayama and Rafter, 1999;Wollowski et al, 2001].…”
Section: Introductionmentioning
confidence: 97%
“…Lactic acid bacteria (LAB) and their fermented products are thought to confer a variety of important nutritional and therapeutic benefits (e.g., relief of lactose maldigestion, antidiarrhoeal capabilities) [Tuohy et al, 2003]. Moreover, some fermented dairy products and/or LAB have demonstrated antimutagenic/antigenotoxic acti-vities both in vitro and in vivo [Bodana and Rao, 1990;Renner and Munzner, 1991;Hayatsu and Hayatsu, 1993;Pool-Zobel et al, 1993a,b, 1996Villarini et al, 1997;Villarini and Pasquini, 1999] as well as antitumor properties [Hirayama and Rafter, 1999;Wollowski et al, 2001].…”
Section: Introductionmentioning
confidence: 97%
“…Bifidobacteria and lactobacilli are the most widely studied probiotic genera and have been shown to exert cancer protective effects in vitro and in vivo (Lidbeck et al, 1992;Pool-Zobel et al, 1993). These organisms have low activities of enzymes involved in the conversion of procarcinogens into potentially carcinogenic compounds (Nakamura et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…And, the numbers of fecal beneficial and pathogenic bacteria were minimally affected by treatments under the conditions of this experiment. it has also been observed that the oral administration of Bifidobacterium or Lactobacillus organisms improved birth weight gain and mortality in calves fed probiotic supplements compared with control animals (1,23).…”
Section: Change Of Growth Ratementioning
confidence: 91%